Revisiting (Non-)Native Influence in VOT Production: Insights from Advanced L3 Spanish - Raquel Llama; Walcir Cardoso (Languages, 2018)
A growing body of research investigating cross-linguistic influence on the acquisition of a third phonological system suggests that first (L1) and second (L2) languages concur in influencing oral production in the target third language (L3). Yet, there are also claims of either a more noticeable effect of the L2 on the L3, or a prevailing influence from the L1. This study further explores whether the L1 and the L2 compete or converge on exerting influence on L3 pronunciation. To do so, we examine the production of voice onset time for voiceless stops by adult advanced learners of L3 Spanish divided into two groups (15 L1 English-L2 French, and 15 L1 French-L2 English speakers). Three monolingual control groups were also tested. Participants were recorded reading word lists that contained voiceless stops in stressed onset position. A Kruskal-Wallis test uncovered significant differences traceable to the L1-English speakers, which puts them at a slight disadvantage vis-à-vis their Francophone counterparts. These results favor claims of a more decisive role for the L1 in L3 pronunciation. We compare our results to findings from previous studies targeting intermediate learners, and find proficiency in the L3 may account for the observed differences.